Iklim Komunikasi dan Harmonisasi pada Lembaga Tuha Peut Gampong Suleue Darussalam Aceh Besar - Nurdin, Hanifah; Asmaunizar, Asmaunizar; Yusnadi, Yusnadi; Samosir, Hasrat Efendi; Situmeang, Marini Kristina (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
The tuha peut institution in Suleue Village, Darussalam District, Aceh Besar Regency serve as a legislative body in the village government that functions as a center for supervision, coordination, accommodating aspirations, and formulating qanuns (village regulation). In carrying out its functions since 2020 there have been several cases that have been able to be resolved. Mild to severe cases that are resolved require a good climate of communication and harmonization internally and externally. The research method uses descriptive with a qualitative approach. Participatory observation research technique with observation, interview and documentation data collection methods. The results obtained that tuha peut institutions must strengthen the vision, mission and leadership; accommodate community aspirations; effetively conflict resolution, oversee budget use; and optimize program proposals. A conducive communication climate is fostered by strengthening the both top-down and bottom-up communication lines internally and externally.